Swot Analysis For Determining The Company's Position In Business Sustainability - Muhammad Rafly; Rini Rahayu Kurniati; Ainul Chanafi (International Journal of Entrepreneur and Business Administration, 2024)
The purpose of this study is to analyze internal and external factors to determine the position of Tahu Sutra Presta Jaya MSME in business sustainability using SWOT analysis. This research method uses a mix method. Data collection techniques in this study through interviews, questionnaires, observation and documentation. Qualitative data analysis techniques use the Miles and Hubberman model while quantitative data analysis techniques use SWOT analysis. The results of this study indicate that the position of Tahu Sutra Presta Jaya MSME in the SWOT diagram is in quadrant I which supports an aggressive strategy. The strategies that can be applied in these conditions are the Strengths-Opportunities, SO strategy.